HUKUM PIDANA KORUPSI DAN HUKUM ADMINISTRASI NEGARA PULAU-PULAU KECIL PERBATASAN - Rovsky Wattimena; Welmince Arloy; Manery, Nugrah Gables; Hery Albert Gardjalay; Maher Lawalata; Johan Rumangun; Jondry Unwawirka; Yanes Wamona; Abner Kadalolor (Asosiasi Dosen Muda Indonesia, 2023)
The government system in Indonesia is organized in stages starting from the central government, provincial, district/city and village governments. All government affairs are divided into each level of government. The village government is the spearhead that has direct contact with the community in real terms. Historically, the existence of villages in Indonesia existed before the Unitary State of the Republic of Indonesia existed or was formed, therefore, if you look at Law No. 6 of 2014 concerning Villages, it is stated that Villages are Villages and traditional villages or referred to by other names, hereinafter referred to as Villages, is a legal community unit that has territorial boundaries that has the authority to regulate and manage government affairs, the interests of local communities based on community initiatives, rights of origin, and/or traditional rights that are recognized and respected in the government system of the Unitary State of the Republic of Indonesia. Openness in the administration of village government is absolutely necessary as a form of accountability for all decisions and policies that have been taken and implemented related to the implementation of development, community development and community empowerment. Openness is needed to increase community participation in development by providing input, support and control over the running of village government. The reality on the ground is that in 2015 the consequence of implementing the Village Law was that funds were disbursed from the APBN which were quite large at the village level, however openness regarding the implementation of village funds was very minimal until now, the human resource capacity of village officials was very minimal. so that it greatly influences the management and management of village funds to create an independent and prosperous village community based on the principles of good governance, namely accountability, transparency and participation.